2018
DOI: 10.1002/ece3.4760
|View full text |Cite
|
Sign up to set email alerts
|

Potential of a no‐take marine reserve to protect home ranges of anadromous brown trout (Salmo trutta)

Abstract: The extent to which no‐take marine reserves can benefit anadromous species requires examination. Here, we used acoustic telemetry to investigate the spatial behavior of anadromous brown trout (sea trout, Salmo trutta) in relation to a small marine reserve (~1.5 km2) located inside a fjord on the Norwegian Skagerrak coast. On average, sea trout spent 42.3 % (±5.0% SE) of their time in the fjord within the reserve, a proportion similar to the area of the reserve relative to that of the fjord. On average, sea tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…In the latter case movement may only be as far as the estuary, with some authors referring to this as semi‐anadromy or partial‐anadromy, but, confusingly, these terms are also used by other authors in the sense of facultative migration. In Denmark and Norway migration can be terminated in a fjord rather than continue to the open sea (del Villar‐Guerra et al ., ; Thorbjørnsen et al ., ). Some authors (Quinn, ) use a more abbreviated terminology for potamodromy simply referring to adfluvial for migrations between natal rivers and lakes and fluvial both for migrations within rivers and river‐residents.…”
Section: Introductionmentioning
confidence: 97%
“…In the latter case movement may only be as far as the estuary, with some authors referring to this as semi‐anadromy or partial‐anadromy, but, confusingly, these terms are also used by other authors in the sense of facultative migration. In Denmark and Norway migration can be terminated in a fjord rather than continue to the open sea (del Villar‐Guerra et al ., ; Thorbjørnsen et al ., ). Some authors (Quinn, ) use a more abbreviated terminology for potamodromy simply referring to adfluvial for migrations between natal rivers and lakes and fluvial both for migrations within rivers and river‐residents.…”
Section: Introductionmentioning
confidence: 97%
“…However, the potential for protection depends on the location of the home range. Thorbjørnsen et al (2019) showed that the degree of potential protection conferred to sea trout by a no-take zone increased with home range size in sea trout initially tagged outside of the no-take zone (Figure 3B). Last, movement traits must be at least partially heritable to affect population behavioral composition over time, which seems to be the case across species and taxa according to a recent metanalysis by Dochtermann et al (2019).…”
Section: Behavioral Traitsmentioning
confidence: 97%
“…Surrounded by MPAs allowing hook-and-line-type fishing gear, the no-take zone enables studying effects of protection on fish (Figure 1 and Table 1). An acoustic telemetry array consisting of 56 acoustic receivers is deployed in the fjord, also including the no-take zone (for details, see Villegas-Ríos et al, 2017b;Thorbjørnsen et al, 2019;Freitas et al, 2021).…”
Section: Study Systemmentioning
confidence: 99%
See 2 more Smart Citations